First clues on the ecology of whale falls in the deep Atlantic Ocean: results from an experiment using cow carcasses. (August 2015) - Hilario, Ana; Cunha, Marina R.; Génio, Luciana; Marçal, Ana Raquel; Ravara, Ascensão; Rodrigues, Clara F.; Wiklund, Helena
Abstract: Sunken whale carcasses, known as 'whale falls', deliver large pulses of organic material to the seafloor and serve as habitat islands for unique assemblages of deep‐sea fauna that include generalist scavenging species, chemosynthetic fauna related to those from hydrothermal vents and cold seeps, and bone‐specialist species. Despite the growing interest in this peculiar habitat in the last decade, all long‐term studies of deep‐sea whale‐falls have been restricted to the Pacific and the ecology of these habitats in the Atlantic Ocean has been overlooked. Here we report the first study on large mammal carcasses in the deep Atlantic Ocean. Cow carcasses amounting to 570 kg were deployed at 1000 m in the Setubal canyon, where cetaceans naturally occur. Eighteen months after deployment, all soft tissues had been consumed and the visible remains of the carcasses consisted solely of skeletal material that supported a diverse macrofaunal assemblage distinct from that of the background, including organic‐enrichment respondents, sulphophiles and bone‐specialists. The trophic structure of this assemblage denotes an overlap of successional stages previously described in whale falls. Our results provide important insights into the contribution of mammal falls to deep‐sea biodiversity in the NE Atlantic, species distribution and biogeography of bone specialists, and the potential role of these habitats as dispersal stepping‐stones for vent and seep species. Additionally we show that cow carcasses may serve as an accessible model system for the study of ecological processes at deep‐sea whale‐falls.